#### Answer

x = -7

#### Work Step by Step

-3 = 3 (x + 6)
Step 1 : Use the distributive property on the right side of the equation.
3(x + 6) = 3*x + 3*6 or 3x + 18
Now the equation looks like this.
- 3 = 3x + 18
Step 2: Combine like terms. Check the left side of the equation. There are no like terms. Check the right side. No like terms there either, so go on to Step 3.
Step 3: Subtract -18 to both sides to get the variable term by itself on the right side
-3 - 18 = 3x +18 - 18
-21 = 3x
Step 4 : Divide both sides by 3.
$\frac{-21}{3}$ = $\frac{3x}{3}$
-7 = x
Step 5: Check. Go back to the original equation
- 3 = 3x + 18
Replace y with -7
-3 = 3*-7 + 18
-3 = -21 + 18
-3 = -3
True, so -7 is the correct solution